History of Deer Herd Reduction for Tick Control on Maine’s Offshore Islands - Elias, Susan; Stone, Benjamin; Rand, Peter; Lubelczyk, Charles; Smith, Robert (Maine Policy Review, 2021)
The incidence of Lyme disease in Maine is associated with high abundance of blacklegged (deer) ticks, which in turn has been partly attributed to local overabundance of white-tailed deer. With evidence from Monhegan Island that the complete removal of deer reduced ticks and risk of contracting Lyme disease, nine other offshore communities initiated efforts to cull deer. We reviewed and summarized available histories of deer management on Maine’s offshore islands. Concern about Lyme disease provided the overarching impetus for deer culls. Culls mostly occurred on islands that have no regular firearms hunting season, island communities have been challenged to control deer numbers, and social acceptance of deer culls varied. Integrated tick management (ITM) is the key to controlling ticks, but statewide ITM policy is lacking. Formation of vector control districts with statewide ITM policy would support all communities in Maine.